Zomato And the Indian Appetite : A Study of Online Food Ordering Preferences - Harsh Bhadouriya; Dr. Jaideep Sharma (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
India's food delivery sector has witnessed unprecedented growth, propelled by technological innovation, urban lifestyles, and a rising demand for convenience. Dominated by platforms like Zomato and Swiggy, the industry has redefined how consumers access meals, supported by smartphone penetration, digital payment systems like UPI, and pandemic-driven shifts. Zomato's journey—from a 2008 menu aggregator to a diversified food-tech giant—illustrates the sector's dynamic evolution. However, understanding consumer preferences across India’s diverse demographics remains a key challenge. This study investigates the primary factors shaping customer satisfaction and loyalty on Zomato, focusing on delivery quality, app usability, offers, hygiene, and regional behaviour. The research aims to provide actionable insights for improving personalized strategies, ensuring sustained growth and competitive edge in the post-pandemic food delivery ecosystem.